Introduction to the Section: Widening the Scope of Psychodynamic Child and Adolescent Psychotherapy Research: Recent Applications and New Directions. Issue 1 (31st December 2022) - Halfon, Sibel
ABSTRACT: Recent developments in psychodynamic work with children and adolescents have made empirical research a higher priority in the field. In order to support the evidence-base of psychodynamic child and adolescent psychotherapy, more research is needed to identify the underlying therapeutic processes that make psychodynamic psychotherapy effective for different kinds of children and adolescents and contribute to the literature on therapeutic mechanisms of change. Drawing on the expertise of a range of contributors, this special section describes recent child and adolescent psychodynamic psychotherapy research illustrating a range of quantitative and qualitative methodologies that have been developed to investigate different clinical phenomena, processes of psychotherapy and outcome. These papers will serve as a vital resource helping researchers and clinicians develop clinically relevant research agendas to improve clinical practice and care with children and adolescents.